2012
DOI: 10.1155/2012/504590
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of Combustion and Knock in a Dual Fuel Gas/Diesel Compression Ignition Engine

Abstract: Conventional compression ignition engines can easily be converted to a dual fuel mode of operation using natural gas as main fuel and diesel oil injection as pilot to initiate the combustion. At the same time, it is possible to increase the output power by increasing the diesel oil percentage. A detailed performance and combustion characteristic analysis of a heavy duty diesel engine has been studied in dual fuel mode of operation where natural gas is used as the main fuel and diesel oil as pilot. The influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…With the aid of electronic controllers, HPCR system allows adjustment of injection pressure, fuel injection amount, injection timing, and injection pulse number in each combustion cycle very flexibly [1][2][3]. Then optimized injection strategies can improve diesel engine combustion for low combustion noise, high combustion efficiency, and low emissions [4,5]. It can also provide postinjection for helping after-treatment system for regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of electronic controllers, HPCR system allows adjustment of injection pressure, fuel injection amount, injection timing, and injection pulse number in each combustion cycle very flexibly [1][2][3]. Then optimized injection strategies can improve diesel engine combustion for low combustion noise, high combustion efficiency, and low emissions [4,5]. It can also provide postinjection for helping after-treatment system for regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In [21], the authors studied the effect of different boost levels on the dual fuel engine performance and as expected the increase in boost level results in an increase in the dual fuel engine power output. However, as intake pressure and temperature increase, knock tendency increases as well.…”
Section: Intake Charge Conditioningmentioning
confidence: 90%
“…The reviewed papers [21,23] showed that the intake temperature increase leads to an increase in combustion efficiency. As the intake air temperature is increased, air mass inside the cylinder decreases which leads to a decrease in the premixed excess air ratio, which in combination with higher temperatures leads to more complete flame propagation.…”
Section: Intake Charge Conditioningmentioning
confidence: 99%
“…Gharehghani et al [25] reported that by increasing the intake swirl ratio in dual-fuel engines, a significant reduction in NOx was achieved at high engine load with lower mass ratio of natural gas, while lower PM was recorded at lower load and higher mass ratio of natural gas. At part load, the total bsfc was considerably higher under dual-fuel mode due to the low combustion rate of gaseous fuel.…”
Section: Cng-co2/diesel Dual-fuel Combustionmentioning
confidence: 99%